2006
DOI: 10.1111/j.1365-2672.2005.02753.x
|View full text |Cite
|
Sign up to set email alerts
|

First isolation of Shiga toxin 1d producing Escherichia coli variant strains in shellfish from coastal areas in France

Abstract: Aims:  This study was carried out to evaluate the presence of Shiga toxin‐producing Escherichia coli (STEC) and E. coli O157:H7 in shellfish from French coastal environments. Methods and Results:  Shellfish were collected in six growing areas or natural beds (B category) and nonfarming areas (D category) from July 2002 to August 2004. PCR detection of stx genes was performed on homogenized whole shellfish and digestive gland tissues enrichments. STEC strains were detected by colony DNA hybridization using a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 70 publications
(139 reference statements)
2
55
0
3
Order By: Relevance
“…Most of the strains used in this study were isolated between February 2013 and January 2015 from three French shellfish-harvesting areas and their watersheds, located on the English Channel coast (47). Three strains were isolated from other French shellfish-harvesting areas in 2006 (48). A total of 28 STEC and 75 EPEC strains belonging to 68 distinguishable serotypes isolated from three types of shellfish (oysters, mussels, and cockles) and from freshwater, seawater, and surface sediment samples were investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the strains used in this study were isolated between February 2013 and January 2015 from three French shellfish-harvesting areas and their watersheds, located on the English Channel coast (47). Three strains were isolated from other French shellfish-harvesting areas in 2006 (48). A total of 28 STEC and 75 EPEC strains belonging to 68 distinguishable serotypes isolated from three types of shellfish (oysters, mussels, and cockles) and from freshwater, seawater, and surface sediment samples were investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Shellfish, due to their filter feeding ability, pose a significant risk to human infection since they can concentrate and retain pathogens (4,130). Numerous studies have reported the recovery of both O157 and non-O157 STEC from the carcass of fish and shellfish offered for sale (131)(132)(133)(134)(135).…”
Section: Fish and Shellfishmentioning
confidence: 99%
“…Dead-end hosts, as the name suggests, are incapable of transmitting STEC naturally to other animals. In the absence of evidence that aquatic species such as finfish and shellfish transmit the organism to other animals, they may act as dead-end hosts for STEC, only transmitting STEC when they are consumed (4)(5)(6).…”
mentioning
confidence: 99%
“…Gourmelon et al [38] suggested that shellfish collected in coastal environments can serve as a vehicle for Shiga toxin-producing E. coli transmission. These authors analyzed samples of mussels (Mytilus edulis and Mytilus galloprovincialis), oysters (Crassostrea gigas) and cockles (Cerastoderma edule) collected from coastal and estuarine environments, and performed the first isolation of ETEC stx1d strains in France.…”
Section: Escherichia Coli In Shellfishmentioning
confidence: 99%